PEER TO PEER LENDING : GENERATION Z ATTRACTION FACTORS AND FUTURE IMPLICATIONS - Panjaitan, Felisia; Setowati, Servatia Mayang; Mahulete, Yoshia Christian (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study is about the factors of behavioral intention to borrow from the perspective of Generation Z toward peer-to-peer lending. This study applied primary data by collecting surveys distributed to Gen Z on Java Island. The sample used was 44 male respondents and 110 female respondents. Factors that influence borrowing intention were tested with SEM PLS 4.0. The research shows that the variables of utilitarian value, risk perception, and financial literacy are significant to the behavioral intention of Peer To Peer Lending. In addition, the findings show that the variables of convenience and safety do not determine behavioral intention in Peer To Peer Lending. This research also explores how financial technology, such as peer-to-peer lending, can facilitate Generation Z's access to finance. The implications of this research highlight the importance of financial knowledge and planning for Gen Z for its future. These findings provide insights for fintech companies to design products and services that suit Generation Z's specific preferences and needs. The target market for peer-to-peer lending companies needs to be adjusted in their marketing strategies.